Relationship of Exclusive Breastfeeding with The Incidence of Acute Respiratory Infections in Toddlers at The Ringinarum Health Center Kendal Regency - Izza Alya Ardana Putri; Astin Prima Sari; Ika Dyah Kurniati (Magna Medika, 2023)
Background: Acute Respiratory Infection (ARI) is an acute infection affecting the nose, paranasal sinuses, pharynx, trachea, bronchi, lungs, and epiglottis. ARI is the main cause of mortality and morbidity in toddlers in the world. The incidence of ARI can be prevented by exclusive breastfeeding.